2020
DOI: 10.3390/f11050494
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Pattern of Stem Diameter Growth of Qinghai Spruce in the Qilian Mountains, Northwestern China

Abstract: It is important to develop a better understanding of the climatic and soil factors controlling the stem diameter growth of Qinghai spruce (Picea crassifolia Kom.) forest. The results will provide basic information for the scientific prediction of trends in the future development of forests. To explain the seasonal pattern of stem diameter growth of Qinghai spruce and its response to environmental factors in the Qilian Mountains, northwest China, the stem diameter changes of 10 sample trees with different sizes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 45 publications
1
20
1
2
Order By: Relevance
“…Elevation, as a natural simulant of future climates [11], has a strong impact on local climate conditions, and seasonal patterns of stem growth and climate-growth relationships may vary with elevation, such as variations in temperature and precipitation [12][13][14]. Many studies have reported that intra-annual stem growth for the same tree species had divergent across elevations; i.e., the growth initiation was linearly delayed and nearly synchronous with increasing elevations, which was primarily controlled by temperature [14][15][16][17]; however, the growth cessation was no consensus across elevations, which was predominately controlled by photoperiod and an earlier cell differentiation [15,18,19], while was influenced by soil moisture deficit in arid and semi-arid regions [17,[20][21][22]. Although there is still much uncertainty about intra-annual stem growth at different elevations, how seasonal patterns of stem growth is controlled by climatic and soil conditions at different elevations has rarely been studied in dryland montane forests of northwestern China.…”
Section: Introductionmentioning
confidence: 99%
“…Elevation, as a natural simulant of future climates [11], has a strong impact on local climate conditions, and seasonal patterns of stem growth and climate-growth relationships may vary with elevation, such as variations in temperature and precipitation [12][13][14]. Many studies have reported that intra-annual stem growth for the same tree species had divergent across elevations; i.e., the growth initiation was linearly delayed and nearly synchronous with increasing elevations, which was primarily controlled by temperature [14][15][16][17]; however, the growth cessation was no consensus across elevations, which was predominately controlled by photoperiod and an earlier cell differentiation [15,18,19], while was influenced by soil moisture deficit in arid and semi-arid regions [17,[20][21][22]. Although there is still much uncertainty about intra-annual stem growth at different elevations, how seasonal patterns of stem growth is controlled by climatic and soil conditions at different elevations has rarely been studied in dryland montane forests of northwestern China.…”
Section: Introductionmentioning
confidence: 99%
“…The mean annual sunshine duration was 1892.6 h•a −1 . The mean annual relative humidity was 60% [26,28].…”
Section: Study Areamentioning
confidence: 99%
“…The soil in the plot was thick and highly permeable, with an average soil thickness of 70 cm. The soil type was mountainous grey cinnamon soil and its texture was loam, with sand content of 34%, a total soil porosity of 71.2%, and a bulk density of 0.83 g•cm −3 in the root zone (0 to 60 cm soil layer) [28,34]. Within the 0 to 60 cm root zone, the saturation moisture content was approximately 0.69 m 3 •m −3 and the field capacity was approximately 0.58 m 3 •m −3 [28,34].…”
Section: Research Plotmentioning
confidence: 99%
See 1 more Smart Citation
“…The vegetation cover was mainly alpine meadow and alpine steppe grasslands, dominated by sedges Kobresia pygmaea , Kobresia tibetica , and Kobresia humilis , and Stipa purpurea grass [ 24 ]. The region is characterized by an alpine semi-arid climate with an annual precipitation of approximately 430 mm, and an annual potential evaporation of about 1080 mm [ 25 26 ]. About 90% of precipitation falls as rain from May to September, with snowfall contributing less than 10% [ 25 ].…”
Section: Study Descriptionmentioning
confidence: 99%